2014
DOI: 10.1016/j.cell.2014.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Circadian Output Circuit for Rest:Activity Rhythms in Drosophila

Abstract: SUMMARY Though much is known about the cellular and molecular components of the circadian clock, output pathways that couple clock cells to overt behaviors have not been identified. We conducted a screen for circadian-relevant neurons in the Drosophila brain, and report here that cells of the pars intercerebralis (PI), a functional homologue of the mammalian hypothalamus, comprise an important component of the circadian output pathway for rest:activity rhythms. GRASP analysis demonstrates that PI cells are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
274
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(304 citation statements)
references
References 59 publications
(72 reference statements)
14
274
3
Order By: Relevance
“…Of the different groups of peptidergic cells in the PI, those that secrete DH44 and SIFamide are relevant for rest:activity rhythms. Manipulation of IPCs does not disrupt circadian locomotor rhythms (Cavanaugh et al 2014), but we found through GFP reconstitution across synaptic partners (GRASP) experiments that, like the DH44 cells, IPCs physically connect to DN1 cells of the clock network (Fig. 1A).…”
Section: Ipcs Represent a Metabolic Clock Output Regionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the different groups of peptidergic cells in the PI, those that secrete DH44 and SIFamide are relevant for rest:activity rhythms. Manipulation of IPCs does not disrupt circadian locomotor rhythms (Cavanaugh et al 2014), but we found through GFP reconstitution across synaptic partners (GRASP) experiments that, like the DH44 cells, IPCs physically connect to DN1 cells of the clock network (Fig. 1A).…”
Section: Ipcs Represent a Metabolic Clock Output Regionmentioning
confidence: 99%
“…Brains expressing GFP1-10 in IPCs under the control of the Gal4-UAS system (DILP2-Gal4>UAS-GFP1-10) and GFP11 in DN1 neurons under the control of the LexAop system (Clk4.1-LexA>-LexAop-GFP-11) were imaged via confocal microscopy to assess GFP fluorescence (Cavanaugh et al 2014).…”
Section: Graspmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Interestingly, neurons expressing Diuretic Hormone 44 (DH44) in the PI have been implicated in both the regulation of activity-rest rhythms 39 and the detection and consumption of nutritive sugars, 40 which suggests that multiple neuronal groups may be involved in the coordination of sleep and metabolism. Both PL and PI regions are proposed to be analogous to the mammalian hypothalamus, 41 a major sleep and feeding center.…”
Section: Figure 2 Tara and E2f1 Appear Not To Interact For Sleep Regmentioning
confidence: 99%